A cost comparative study of Gamma Knife radiosurgery versus open surgery for intracranial pathology. Issue 1 (January 2015) - Caruso, James P.; Moosa, Shayan; Fezeu, Francis; Ramesh, Arjun; Sheehan, Jason P.
Abstract Resection is the traditional treatment for common intracranial pathologies including brain metastases, arteriovenous malformations (AVM), and acoustic neuromas. However, more recently Gamma Knife radiosurgery (GKRS; Elekta AB, Stockholm, Sweden) has emerged as an effective, alternative treatment modality. There are limited data investigating the cost effectiveness of these two treatment modalities. In this study, we compare the costs of GKRS and open surgical excision. This was a retrospective study including all patients at a single-institution across a 3 year period with at least 12 months of post-resection follow-up for brain metastases, acoustic neuromas, or AVM. The costs of care were then totaled and compared to known average costs for GKRS at the same institution. The average 12 month costs of treating patients with brain metastases, acoustic neuromas, and AVM using open surgery were USD55, 938, 67, 538, and 78, 332, respectively. The average 12 month costs of treating brain metastases, acoustic neuromas, and AVM with GKRS were USD23, 069, 37, 840, and 46, 293, respectively. This shows that GKRS was on average 58.8%, 44.0%, and 40.9% of the cost of open surgery for brain metastases, acoustic neuromas, and AVM, respectively. GKRS is a cost effective, first-line, alternative to open surgery for treatment of brain metastatic lesions, acoustic neuromas, and AVM in selected patients. This result conforms to previous studies, which also demonstrate that radiosurgery is the more cost-effective treatment for brain metastases and acoustic neuromas when patients are well suited for either approach. Further prospective studies are needed to show that this result is valid at other institutions.